TIME AND STRAIN DEPENDENCY OF PILE STIFFNESS: IMPACT ON PILE BEHAVIOR AND PILE LOADING TESTS RESULTS - Szymkiewicz, Fabien; Mohamad, Wassim; Elayni, Nader; Minatchy, Carlos (GEOMATE Journal, 2023)
Static pile loading tests are carried out for different purposes: feed extended databases from which design bearing capacity of piles are derived, control the design, develop new piling methods, but also in some cases better understand the behaviour of a deep foundation submitted to additional solicitations such as temperature variations, in the case of geothermal foundations systems. These tests are conducted on any type of piles, themselves made from very different materials. For cast-in-place piles made of a combination of cementitious materials (either cement paste, mortar or concrete for example) and steel, the stiffness of the pile is a combination of the stiffnesses of the different materials. Furthermore, cementitious materials are well known to be evolutive materials, especially regarding their strength. By contrast, the strain, stress and time dependency of the stiffness of the cast-in-place piles is not so well known, and therefore generally not taken into account when analysing static pile loading tests. The aim of this publication is to impart the importance of the evolution of pile stiffness with time and under stress, through different practical examples, and comparisons are made with results obtained with more classical analysis methods.